1983
DOI: 10.1002/1097-0142(19830801)52:3<550::aid-cncr2820520327>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Necrosis as a prognostic criterion in malignant supratentorial, astrocytic gliomas

Abstract: Surgical specimens of malignant, supratentorial, astrocytic gliomas from 503 patients randomized on an RTOG‐ECOG treatment protocol were examined by central pathologic review. The diagnosis of glioblastoma multiforme (GBM) was made only when one or more foci of coagulation necrosis involving astrocytic tumor cells were identified histologically. Malignant astrocytic neoplasms without necrosis were classified as astrocytoma with atypical or anaplastic features (AAF). The median survival stratifying for treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
56
1
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(65 citation statements)
references
References 3 publications
6
56
1
2
Order By: Relevance
“…25,26 In contrast, coagulative necrosis represents the majority of cell death in GBMs and its degree is inversely related to patient survival. 2,27,28 The mere presence of focal necrosis remains one of the strongest independent markers of poor prognosis. 7,29,30 Coagulative necrosis is seen Vaso-occlusion, hypoxia, and necrosis in glioblastoma DJ Brat and EG Van Meir pathologically as either microscopic foci with surrounding pseudopalisading cells ('pseudopalisading necrosis') or as large confluent expanses of dying tumor and nontumor elements.…”
Section: Necrogenesis In Gbmmentioning
confidence: 41%
“…25,26 In contrast, coagulative necrosis represents the majority of cell death in GBMs and its degree is inversely related to patient survival. 2,27,28 The mere presence of focal necrosis remains one of the strongest independent markers of poor prognosis. 7,29,30 Coagulative necrosis is seen Vaso-occlusion, hypoxia, and necrosis in glioblastoma DJ Brat and EG Van Meir pathologically as either microscopic foci with surrounding pseudopalisading cells ('pseudopalisading necrosis') or as large confluent expanses of dying tumor and nontumor elements.…”
Section: Necrogenesis In Gbmmentioning
confidence: 41%
“…However, the incidence and natural history of hypoxia in human brain tumours before and during radiotherapy is poorly understood. The benefit of the use of hypoxic cell radiosensitizers with radiotherapy for gliomas was has been reported for metronidazole (Urtasun et al, 1976) but not for misonidazole (Bleehen et al, 1981;Nelson D et al, 1983;Green et al, 1984).…”
mentioning
confidence: 98%
“…Malignant gliomas are highly cellular tumours which normally contain necrosis (Nelson J et al, 1983;Wilden et al, 1987) and which are commonly assumed to contain substantial numbers of hypoxic cells. Almost all macroscopic transplanted tumours in rodents contain viable hypoxic cells, which are a major cause of radioresistance (Moulder and Rockwell, 1984;Rockwell and Moulder, 1990).…”
mentioning
confidence: 99%
“…As a result of the studies which have demonstrated the importance of necrosis and pointed to MA patients' comparatively shorter survival times (4, 8,11,25), necrosis has become an important diagnostic criterion in GM for many pathologists. The presence or absence of necrosis is a key criterion in diagnosing the most anaplastic form of GBM (25). However, the proportion of GBM without histopathological necrosis is reported to be 8-34% in the literature (4).…”
Section: Ekici Ma Et Al: Analysis Of the Mortality Probability Of Prmentioning
confidence: 99%